The Effect of Standardized Fartlek Training Using Resistance To Develop Speed Endurance In Youth Cyclists - gareeb , maan (Journal of Physical Education, 2010)
The sport of cycling in general and road cycling in particular is one of the open sports. Many factors play important roles on the performance of cyclists like the wind, temperature, environment, etc. It is extremely important to overcome these variables using various training methods as well as developing necessary abilities. The importance of the research lies in developing special endurance in cyclist using resistance on the wheels. The researcher used the experimental method. The subjects were (8) cyclist divided into two equal groups the experimental group and the controlling group. The researcher finally came up with the conclusions and recommendations.